Optimal Winter and Summer Settings of Solar Photovoltaic Panels for Many Locations in the World - Dr. Aqeel Salih (Tikrit Journal of Pure Science, 2024)
An increasing interest in the use of solar energy to generate electricity for several applications has stimulated a need for studying optimal settings of photovoltaic panels. The photovoltaic panel performance is highly affected by its direction and its tilt angle. This research calculates the optimal tilt angles of photovoltaic panels for 60 locations in 60 countries around the world. These angles are calculated from vertical using Solar Irradiance Calculator. The optimal tilt angle for the studied locations ranges from (15°) to (57°) and (45°) to (87°) in winter and summer, respectively. It is shown that the angles that are obtained from equations are very close to those calculated from the calculator. This study is very useful to find the optimal tilt angle at any location by knowing only its latitude. The results can be extended to any location in the world. This research is intended to be used as a guidance for using photovoltaic panels